-7(-5x+7)=-49

Simple and best practice solution for -7(-5x+7)=-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-5x+7)=-49 equation:


Simplifying
-7(-5x + 7) = -49

Reorder the terms:
-7(7 + -5x) = -49
(7 * -7 + -5x * -7) = -49
(-49 + 35x) = -49

Add '49' to each side of the equation.
-49 + 49 + 35x = -49 + 49

Combine like terms: -49 + 49 = 0
0 + 35x = -49 + 49
35x = -49 + 49

Combine like terms: -49 + 49 = 0
35x = 0

Solving
35x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '35'.
x = 0

Simplifying
x = 0

See similar equations:

| 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 | | 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 | | 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 | | -.5=4-4.5x | | 4x+(-3)=1 | | 11q=33 | | y=0.80(55)+136 | | 4x+(-3)=2 | | 8x-2=-9+7y | | .3(3x+6)=8x+10 | | 5(6+3x)=105 | | -5y+6=y+9 | | (-9-12)x=8-4x | | y=0.80(45)+136 | | 5x+-2x+5x=8 | | 20/(-4)=c | | x^2+x+30=0 | | .75x-1.25=-2 | | 64y^3-2=y-128y^2 | | 3h-15+h=5.2 | | y=0.80(35)+136 | | 3x-6=8(x-9) |

Equations solver categories